The comorbidity of depression and neurocognitive disorder in persons with HIV infection: call for investigation and treatment - Goodkin, Karl; Evering, Teresa H.; Anderson, Albert M.; Ragin, Ann; Monaco, Cynthia L.; Gavegnano, Christina; Avery, Ryan J.; Rourke, Sean B.; Cysique, Lucette A.; Brew, Bruce J. (Frontiers in Cellular Neuroscience, 2023)
Depression and neurocognitive disorder continue to be the major neuropsychiatric disorders affecting persons with HIV (PWH). The prevalence of major depressive disorder is two- to four-fold higher among them than in the general population (~ 6.7%). Prevalence estimates of neurocognitive disorder among PWH range from 25% to over 47% -- depending upon the definition used (which is currently evolving), the size of the test battery employed, and the demographic and HIV disease characteristics of the participants included, such as age range and sex distribution. Both major depressive disorder and neurocognitive disorder also result in substantial morbidity and premature mortality. However, though anticipated to be relatively common, the comorbidity of these two disorders in PWH has not been formally studied. This is partly due to the clinical overlap of the neurocognitive symptoms of these two disorders. Both also share neurobehavioral aspects - particularly apathy - as well as an increased risk for non-adherence to antiretroviral therapy. Shared pathophysiological mechanisms potentially explain these shared phenotypes, including neuroinflammatory, vascular, microbiomic, and neuroendocrine/neurotransmitter dynamic mechanisms. Treatment of either disorder affects the other with respect to symptom reduction as well as medication toxicity. Deficits in dopaminergic transmission occur in both major depressive disorder and HIV-associated neurocognitive disorder. Specific treatment for the comorbidity that restores dopaminergic transmission may be indicated and merits study.